2002
DOI: 10.1128/aem.68.4.1595-1603.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Method To Assess the Diversity of Burkholderia Species in Environmental Samples

Abstract: In spite of the importance of many members of the genus Burkholderia in the soil microbial community, no direct method to assess the diversity of this genus has been developed so far. The aim of this work was the development of soil DNA-based PCR-denaturing gradient gel electrophoresis (DGGE), a powerful tool for studying the diversity of microbial communities, for detection and analysis of the Burkholderia diversity in soil samples. Primers specific for the genus Burkholderia were developed based on the 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 49 publications
(39 reference statements)
9
69
0
7
Order By: Relevance
“…B. cepacia complex was the most frequently isolated microorganism and recA-RFLP pointed to a polyclonal nature of the outbreak, which was confirmed by other molecular typing data. The results are consistent with bacterial diversity found in environmental samples (Salles et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…B. cepacia complex was the most frequently isolated microorganism and recA-RFLP pointed to a polyclonal nature of the outbreak, which was confirmed by other molecular typing data. The results are consistent with bacterial diversity found in environmental samples (Salles et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…The Pseudomonas-specific primer sets used were PSf (5 0 -GGTCTGAGAGGATGATCAGT-3 0 ) and PSr (5 0 -TTAGCTCCACCTCGCGGC-3 0 ) (Widmer et al, 1998). The Burkholderia-specific primer sets used were Burk3 (5 0 -CTGCGAAAGCCGGAT-3 0 ) and BurkR (5 0 -TGCCATACTCTAGCYYGC-3 0 ) (Salles et al, 2002). For quantification of Trichoderma spp., we used a modified protocol of Hagn et al (2007).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The nested PCR reactions were performed for Burkholderia spp. with primers Burk3 and R1378 (Salles et al, 2002). The products from the first PCR were diluted at 1:1000 and used as the template in the second PCR with primers Burk3-GC and BurkR (Salles et al, 2002).…”
Section: Pcr-dgge Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the case of the rhizosphere, several microbial groups, such as Burkhoderia and Pseudomonas, have been shown to be important community members and specific primer sets have thus been developed for these species (Salles et al 2002;Gyamfi et al 2002). Holben et al (2004) reported the use of DGGE in combination with GϩC fractionation to assess microbial community diversity and to detect minority populations of bacteria in the digestive tracts of chickens.…”
Section: Potential Biases In Pcr Amplificationmentioning
confidence: 99%